ОБ ОДНОМ ДОКАЗАТЕЛЬСТВЕ ТЕОРЕМЫ ЛИУВИЛЛЯ НА ПЛОСКОСТИ - Нарекеев, Б.; Мырзанова, Д. (SCIENCE and SOCIETY, 2016)
The article is devoted to the definition of transfinite diameter, the conform module and transfinite module of the condenser, the theoreme of Liouvill, which is proved by means of T. Begbi’s theorem.